Causal relationships between lung cancer and sepsis: a genetic correlation and multivariate mendelian randomization analysis - Zhou, Jiejun; Zhang, Youqian; Yang, Tian; Zhang, Kun; Li, Anqi; Li, Meng; Peng, Xiaojing; Chen, Mingwei (Frontiers in Genetics, 2024)
Background: Former research has emphasized a correlation between lung cancer (LC) and sepsis, but the causative link remains unclear.Method: This study used univariate Mendelian Randomization (MR) to explore the causal relationship between LC, its subtypes, and sepsis. Linkage Disequilibrium Score (LDSC) regression was used to calculate genetic correlations. Multivariate MR was applied to investigate the role of seven confounding factors. The primary method utilized was inverse variance weighting (IVW), supplemented by sensitivity analyses to assess directionality, heterogeneity, and result robustness.Results: LDSC analysis revealed a significant genetic correlation between LC and sepsis (genetic correlation = 0.325, P = 0.014). Following false discovery rate (FDR) correction, strong evidence suggested that genetically predicted LC (OR = 1.172, 95% CI 1.083~1.269, P = 8.29×10 -5 , Pfdr = 2.49×10 -4 ), squamous cell lung carcinoma (OR = 1.098, 95% CI 1.021~1.181, P = 0.012, Pfdr = 0.012), and lung adenocarcinoma (OR = 1.098, 95% CI 1.024~1.178, P = 0.009, Pfdr = 0.012) are linked to an increased incidence of sepsis. Suggestive evidence was also found for small cell lung carcinoma (Wald ratio: OR = 1.156, 95% CI 1.047~1.277, P = 0.004) in relation to sepsis. The multivariate MR suggested that the partial impact of all LC subtypes on sepsis might be mediated through body mass index. Reverse analysis did not find a causal relationship (P > 0.05 & Pfdr > 0.05).The study suggests a causative link between LC and increased sepsis risk, underscoring the need for integrated sepsis management in LC patients.